Climate change and spatial planning: Starting points for mitigation and adaptation to climate change in regional planning and land use planning - Fleischhauer, Mark; Bornefeld, Benjamin (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
Climate change and spatial planning are connected in two ways. On the one hand, spatial planning can contribute to mitigating climate change, i.e. to the reduction of greenhouse gas emissions. On the other hand, spatial planning also plays an important role in the adaptation to climate change impacts. This article examines by the example of Germany the potential role regional and land-use planning can play in climate change mitigation and adaptation.